Steady-state tracking analysis of the RLS algorithm for time-varying channels: a general state-space approach - Leon, W.S.; Taylor, D.P. (IEEE communications letters, 2003)
We present a general technique for analyzing the steady-state tracking performance of the recursive least squares (RLS) algorithm for estimating Rayleigh fading channels in terms of the mean squared identification error (MSIE) or mean squared deviation (MSD). The technique may be used with a general-order vector-autoregressive (VAR) model. Numerical results obtained using the technique agree closely with experimental results.